The Effect of Operational Audit Implementation and Implementation of Internal Control to the Effectiveness of Health Services - Bramasto, Ari; Pertiwi, Mentari Puteri; Kristiana, Emelia (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2024)
Private hospitals are generally profit-oriented compared to government hospitals, so it is natural for hospitals to provide health services more than because if the performance is the same or below state hospitals (government), then people will have a tendency to choose government hospitals. Hospital performance will be able to run consistently if the planning, implementation, and control of operational audits and internal controls are good. The purpose of the study was to determine the magnitude of the influence of the implementation of operational audits and the implementation of internal control on the effectiveness of health services at Santo Yusup Hospital. The study used a quantitative approach that was analyzed descriptively, and verifiably. The population is outpatients and inpatients at Santo Yusup Hospital Bandung. The samples used were 338 patients. The results of this study stated that operational audit and internal control, each of which had a significant effect on the Quality of Service at Santo Yusup Hospital with a very weak category.